Polo kinase mediates the phosphorylation and cellular localization of Nuf/FIP3, a Rab11 effector. - Brose, L.; Crest, J.; Tao, L.; Sullivan, W. (Molecular Biology of the Cell, 2017)
Animal cytokinesis involves both actin-myosin-based contraction and vesicle-mediated membrane addition. In many cell types, including early Drosophila embryos, Nuf/FIP3, a Rab11 effector, mediates recycling endosome (RE)-based vesicle delivery to the cytokinesis furrow. Nuf exhibits a cell cycle-regulated concentration at the centrosome that is accompanied by dramatic changes in its phosphorylation state. Here we demonstrate that maximal phosphorylation of Nuf occurs at prophase, when centrosome-associated Nuf disperses throughout the cytoplasm. Accordingly, ectopic Cdk1 activation results in immediate Nuf dispersal from the centrosome. Screening of candidate kinases reveals a specific, dosage-sensitive interaction between Nuf and Polo with respect to Nuf-mediated furrow formation. Inhibiting Polo activity results in Nuf underphosphorylation and prolonged centrosome association. In vitro, Polo directly binds and is required for Nuf phosphorylation at Ser-225 and Thr-227, matching previous in vivo-mapped phosphorylation sites. These results demonstrate a role for Polo kinase in directly mediating Nuf cell cycle-dependent localization.